Obesity Factors on The Incidence of Joint Pain of Elderly - Eny Masruroh; Erry Setyadhani (STIKes Patria Husada Blitar, 2021)
Aging is a process that will be experienced by humans according to the cycle of growth and development. Changes both physically and psychologically often cause disorders and health problems that must be resolved. Problems with the physical aspect of the elderly, one of which is a decrease in musculoskeletal function, especially in the joints, often manifest the appearance of joint pain. The presence of joint cartilage damage due to inflammation, as well as an increase in the load on the joints due to excess body weight (obesity) is other factors that often arise. The hip, lumbal, cervical and knee joints are the parts that support the body's weight, so they experience the most problems. The purpose of this study was to determine the correlation between obesity and the incidence of knee joint pain in the elderly. The design of the study was correlational analytic with a cross sectional approach. The sampling was purposive sampling with 50 respondents as the sample. The instrument used was an observation sheet to measure the respondent's obesity variable and to determine the presence of joint pain using an interview form. The measurement results were then processed and bivariate analysis was carried out using the chi square test. The results of the research analysis Showed the value of p = 0.004 and Î± = 0.05, this meant that p < 0.05, so there was a correlation between the level of obesity and the occurrence of joint pain. This was because not only age but also Â increasing body weight cause joint paint. Â The ability of the knee joint to support the body as a whole was getting heavier due to friction of the joint cartilage. From these studies, it can be concluded that in the elderly, excess body weight can affect to the ability of bones and joints and result in joint pain. The health workers should support the elderly so that the elderly avoid the stress.